Meningkatkan Kompetensi Guru dalam Penyusunan RPP yang Baik dan Benar Melalui Pendampingan Berbasis MGMP di SMPN 4 Praya Timur - Kamaludin, Kamaludin (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2016)
This research aimed to know effectiveness of implementing guiding based MGMP in effort to improve teachers’ competence in arranging good and proper lesson plan, which had benefit to improve professionalism of head master and for teachers to improve learning process in classroom. Action hypothesis: improving target teacher’s competence at first grade students of SMP Negeri 4 Praya Timur in academic year 2015/2016 in arranging good and proper lesson plan. This research conducted two cycles, every cycle was two meeting. Step of every cycle was palnning, acting, observing and reflecting. Indicator of completeness in this research was; 1) result of headmasters’ observation even teachers’ observation as long as guiding process had gotten mean score > 4,0, 2) result of teachers’ activities in arranging lesson plan reached > 100% with mean score was> 70,00. Result of research in cycle I mean score of headmasters’ observation was (3,30), mean score of teachers’ observation (3,40) and result of individual work had mean score (66,40) with percentage of completeness (10%). In cycle II mean score of headmasters’ observation was (4,30), mean score of teachers’ observation was (4,20) and mean score of individual work was (94,09) with percentage of completeness (100%). Indicator of completeness had reached; research was stated success and stopped in cycle II. Conclusion; implementing guiding could improve target teachers’ competence at SMP Negeri Praya Timur in arranging good and proper lesson plan. It suggested for headmaster in order to conduct similar research in effort to improve teachers’ competence, and for teachers in order to be able to arrange good and proper lesson plan.